Subordination of Contractual Liability from the Will of Parties in Iran's Civil Code - Saeed Bigdeli (مطالعات فقه و حقوق اسلامی, 2017)
Article 221 of Iran's Civil Code which is related to damages resulting from non-performance of contractual obligations and its terms, doesn't have a clear nature both because it has no clear jurisprudential precedent and because of non-compliance with its foreign analogues. So, what appear in the legal writings are not the same or uniform; some have considered it as resulting from the silence of jurisprudence in the contractual liability and others have argued that the reason for its legislation is to cover the defects of jurisprudential tools governing the compensation. Any of the views expressed, faced with difficulties which are hard to be accepted. According to the author, legislator, for various reasons, has tried to attribute the contractual compensation to the contract and the parties' will; what has different results than other analyses and meanwhile ensuring the rights of the injured and compensation of damages, has also  reasonable practical consequences.